Parkinson’s Disease Detection Using Structural MRI - Özkan, Çiğdem (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Parkinson’s Disease (PD) is the second most encountered neurodegenerative disorder, second only to Alzheimer’s Disease (AD), and the most common movement disorder affecting 1% of people over the age of 60. PD is characterized by progressive loss of muscle control that causes trembling of the limbs and head at rest position, rigidity, slowness, impaired balance, and later on a shuffling gait. As the disease is progressed, difficulties in walking, talking, and completing basic tasks might occur. The causes of PD are unknown, yet it is believed that both the environmental and genetic factors might lead to PD. High-quality images obtained using neuroimaging methods could give beneficial support to the clinicians for evaluating the treatments. Threedimensional magnetic resonance imaging (3D-MRI) has been effectively utilized in the detection of progressive neurodegenerative diseases including PD. Therefore, using neuroimaging techniques with Computer-Aided Diagnosis (CAD) has gained increasing attention in the early and accurate diagnosis of PD. In this thesis, the extensive reviews on the studies of PD detection using MRI data and CAD methods since 2008 are studied. Furthermore, the affected brain regions owing to PD are obtained by using the 3D Volume of Interests (VOIs) and the captured affected brain regions are compared with the regions reported in the-state-of-the-art studies in the last decade. The obtained affected brain regions might shed light on the existing literature on PD diagnosis. In order to build an automatic method for PD detection, machine learning algorithms are applied to the processed neuroimaging data. It is obvious that pre-processing of 3D-MRI scans plays an important role for post-processing. In this thesis, the preprocessing of 3D-MRI data has been performed by using a Voxel-Based Morphometry (VBM) technique which evaluates the whole brain morphology with voxel-by-voxel comparisons. In VBM, some parameters such as covariates need to be defined to build a model for Gray Matter (GM) and White Matter (WM) volumes of Structural MRI (sMRI) datasets. In this thesis, the effects of using different covariates (i.e. total intracranial volume, age, sex and combination of them) on the classification of PD groups from Healthy Controls (HCs) have been studied. Additionally, in order to determine the 3D VOIs, the significant local alterations in GM and WM volumes of PD groups and HCs, a hypothesis either f-contrast or t-contrast need to be defined. In this thesis, the effects of two different hypotheses on PD detection have been investigated. Furthermore, a feature-level fusion technique in which the 3D GM and WM VOIs are combined considering the effects of both GM and WM volumes in PD diagnosis. The voxels extracted from 3D GM, WM, and the combination of GM and WM VOIs are considered as raw features. Even though the feature extraction decreases the number of features in raw data, using an automatic feature selection method from high dimensional feature space is an asset in PD classification. In this thesis, to select the most discriminative attributes from high-dimensional data, all raw features are ranked by using various feature ranking methods such as minimum redundancy maximum relevance, Relief-F, unsupervised feature selection for multi-cluster data, Laplacian score, regularized discriminative feature selection for unsupervised learning, correlation- based feature selection, and feature selection and kernel learning for local learning-based clustering. In order to select the optimal number of top-ranked discriminative features, a Fisher Criterion (FC) is calculated for different sizes of feature vectors and the optimal number of top-ranked features is selected when the vector size maximizes the FC. In order to classify the PD and HC, five different classification algorithms, namely k- nearest neighbor, naive Bayes, ensemble bagged trees, ensemble subspace discriminant, and support vector machines are used. Moreover, a decision fusion technique which combines the binary outputs of all five classifiers by using a majority voting method is investigated to achieve higher performance in PD diagnosis. The experimental results indicate that the proposed methods are reliable approaches that are highly competitive with the state-of-the-art methods in PD classification. Keywords: Parkinson’s disease, structural MRI, covariates, f-contrast, voxel-based morphometry.

ÖZ: Parkinson Hastalığı (PH), Alzheimer Hastalığından (AH) sonra en çok karşılaşılan ikinci norodejeneratif hastalıktır ve 60 yaş üstü insanların %1’ini etkileyen en yaygın hareket bozukluğudur. PH, dinlenme pozisyonundayken bacaklarda ve kafada titremeye, sertliğe, hareketlerde yavaşlamaya, denge bozukluğuna ve daha sonra ayakları yere sürüyerek yürümeye sebep olan zamanla ilerleyen kas kontrolünün kaybıyla tanımlanmaktadır. Hastalık ilerledikçe, yürüme, konuşma ve temel ihtiyaçları giderme zorlukları ortaya çıkabilir. PH’nin sebepleri bilinmemektedir, ancak hem çevresel hem de genetik faktörlerin hastalığa sebep olabileceğine inanılmaktadır. Nöro-görüntüleme yöntemleri kullanılarak elde edilen yüksek kaliteli görüntüler, klinisyenlere tedaviyi değerlendirirken yararlı desteği sunabilirler. Üç boyutlu manyetik rezonans görüntüleme (3B-MRG), PH’yi de içeren zamanla ilerleyen nörodejeneratif hastalıkların teşhisinde etkili bir şekilde kullanılmaktadır. Bu nedenle, PH’nin erken ve kesin teşhisinde, nöro-görüntüleme tekniklerinin bilgisayar destekli tanı ile kullanılması giderek dikkat çekmeye başlamıştır. Bu tezde, PH’nin sebep olduğu etkilenmiş beyin kısımları, 3B ilgili vokseller kullanılarak elde edilmiştir ve elde edilen bu etkilenmiş beyin bölgeleri son on yılda çalışılmış modern yöntemlerden çıkarılan bölgelerle karşılaştırılmıştır. Ayrıca, 2008’den bugüne MRG verileri ve bilgisayar destekli tanı yöntemleri kullanarak, PH teşhisi üzerine yapılan çalışmalar detaylı bir şekilde incelenmiştir. Elde edilen PH tarafından etkilenmiş beyin bölgeleri PH teşhisinde mevcut literatüre ışık tutabilir. PH teşhisinde otomatik bir metot oluşturmak için, otomatik öğrenme algoritmaları işlenmiş nöro-görüntü verilerine uygulanır. 3B-MRG taramalarının on işlemesinin, son işleme üzerinde önemli bir rol oynadığı açıkça görülmektedir. Bu tezde, 3B-MRG verilerinin ön işlemesi, tüm beyin morfolojisini voksel-voksel karşılaştırarak değerlendiren Voksel Tabanlı Morfometri (VTM) tekniği kullanılarak yapılmıştır. VTM tekniğinde, yapısal MRG verisetlerinin gri madde (GM) ve beyaz madde (BM) hacimleri için model oluşturulmasında, kovaryant gibi bazı parametrelerin tanımlanması gerekmektedir. Bu tezde, PH’ye sahip hastalar ile Sağlıklı Bireylerin (SB’lerin) sınıflandırılmasında, farklı kovaryantların (toplam intrakraniyal hacim, yaş, cinsiyet ve bunların kombinasyonu) kullanımının etkileri çalışılmıştır. Ayrıca, PH hastaları ile SB’lerin, GM ve BM hacimleri arasındaki önemli lokal farklılıklar olarak da bilinen 3B ilgili hacimleri belirlemek için, t-kontrast veya f-kontrast olabilen bir hipotez tanımlamak gerekmektedir. Bu tezde, bahsedilen iki farklı hipotezin, PH teşhisi üzerindeki etkileri incelenmiştir. Buna ek olarak, PH teşhisinde GM ve BM hacimlerini birlikte değerlendiren, 3B GM ve BM birleşimi olarak tanımlanan bir kaynak birleştirme tekniği kullanılmıştır. 3B GM, BM ve bu iki hacmin kombinasyonundan elde edilmiş ilgili vokseller, işlenmemiş özellikler olarak ele alınmıştır. Öznitelik bulma yöntemi işlenmemiş verideki özellik sayısını azaltıyor olsa bile yüksek boyutlu öznitelik uzayından, öznitelikleri otomatik olarak seçme yöntemi kullanmak PH teşhisinde olması gereken bir süreçtir. Bu tezde, yüksek boyutlu veriden, en ayırt edici özellikleri seçmek için işlenmemiş tüm özellikler en az artıklık en çok ilgililer, Relief-F, çoklu-kümeli veri için denetlenmemiş öznitelik seçme, Laplas skoru, denetlenmemiş öznitelik öğrenme için düzenlenmiş ayırt edici öznitelik seçme, ilinti tabanlı öznitelik seçme ve lokal öğrenme tabanlı kümeleme için (öznitelik seçme ve çekirdek öğrenme gibi farklı öznitelik sıralama yöntemleri kullanılarak sıralanmıştır. En ayırt edici özellikleri seçmek için, tüm farklı boyutlardaki özellik vektörlerinin bir Fisher kriter değeri hesaplanır ve vektör boyutunun Fisher kriterini maksimum yaptığı anda optimal sayıdaki en ayırt edici özelliklerseçilmiş olur. PH grubu ile SB grubunu sınıflandırmak icin beş farklı sınıflandırma algoritması kullanıldı. Kullanılan bu algoritmalar k-en yakın komşu, Naïve Bayes, topluluk torbalı ağaç, topluluk altuzay ayırtaç ve destek vektor makineleridir. Buna ek olarak, PH teşhisinde daha iyi bir performans elde etmek amacıyla bahsedilen beş farklı sınıflandırma algoritmalarının ikili çıktılarını çoğunluk onayı yöntemi kullanılarak birleştiren bir karar birleştirme tekniği kullanılmıştır. Deneysel sonuçlar, PH sınıflandırması için bu tezde önerilen yöntemlerin modern yöntemlerle ciddi oranda rekabet edebildiğini göstermiştir. Anahtar Kelimeler: Parkinson hastalığı, yapısal MRI, kovaryant, f- kontrast, voksel tabanlı morfometri
Doctor of Philosophy in Electrical and Electronic Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2018. Supervisor: Prof. Dr. Hasan Demirel.
Keywords: Electrical and Electronic Engineering; Parkinson’s disease; structural MRI; covariates; f-contrast; voxel-based morphometry